Urbanismo temprano en la América española - Fernando Vela Cossío (Mélanges de la Casa de Velázquez)
The discovery and conquest of the New World was followed by a firm will of Castile’s Crown to populate it, promoting and strengthening a process of true colonization of the extensive territories. Probably one of the most important instruments of this policy was the city. Between 1492 and 1542, in the very short space of fifty years, the American continent had become an immense constellation of cities, towns and places on which the legitimacy of the distant metropolis was extended through the action of the citizens themselves. One of the most representative examples of this early population in the Indies, and more specifically in Southern America, is the exploration, conquest and colonization of New Castile, to which we will dedicate in this present work a synthetic case study. Cities as renowned as San Miguel (1532), Jauja (1534), Trujillo (1534), Lima (1535), Huamanga (1539), Huanuco (1539), Arequipa (1540) or Santiago de Moyobamba (1540), are some of the foundations of this early period of the Hispanic colonization of Peru.